A high-performing proton-conducting solid oxide fuel cell with layered perovskite cathode in intermediate temperatures. (18th October 2018) - Li, Fengpeng; Tao, Zetian; Dai, Hailu; Xi, Xinguo; Ding, Hanping
Abstract: Proton conducting solid oxide fuel cells (SOFC) show great potential to be applied in electricity generation at intermediate temperature range, attracting the efforts of developing cathode material to further improve the power density by promoting the oxygen reduction reaction. An A-site deficient layered perovskite (PrBa)0.95 (Fe0.9 Mo0.1 )2 O5+δ (PBFM) is synthesized as cathode material for BaCe0.7 Zr0.1 Y0.2 O3 (BCZY) based SOFC. A nanostructured composite electrode is fabricated by infiltrating another cobalt-based perovskite oxide of Sm0.5 Sr0.5 CoO3-δ into PBFM porous structure aiming at improving the overall catalytic reaction towards oxygen reduction. After confirming the chemical compatibility between these two materials, the electrochemical performances of the single cells are measured. With loading amount of 10% Sm0.5 Sr0.5 CoO3-δ Nanoparticles, a peak power density of 532 mW cm −2 is achieved at 700 °C comparing with 359 mW cm −2 for bare PBFM electrode. A short-term stability confirms the durability of this composite electrode in practical working conditions. Highlights: A novel Layered Perovskite Cathode is evaluated for proton-conducting SOFCs. 10. wt% Sm0.5 Sr0.5 CoO3–δ is the most optimized content among all cathodes. At 700 °C, a maximum power density of 532 mWcm −2 is obtained.